Information-Theoretic Channel for Multi-exposure Image Fusion. (8th October 2021) - Hao, Qiaohong; Zhao, Qi; Sbert, Mateu; Feng, Qinghe; Ancuti, Cosmin; Feixas, Miquel; Vila, Marius; Zhang, Jiawan
Abstract: Multi-exposure image fusion has emerged as an increasingly important and interesting research topic in information fusion. It aims at producing an image with high quality by fusing a set of differently exposed images. In this article, we present a pixel-level method for multi-exposure image fusion based on an information-theoretic approach. In our scheme, an information channel between two source images is used to compute the Rényi entropy associated with each pixel in one image with respect to the other image and hence to produce the weight maps for the source images. Since direct weight-averaging of the source images introduce unpleasing artifacts, we employ Laplacian multi-scale fusion. Based on this pyramid scheme, images at every scale are fused by weight maps, and a final fused image is inversely reconstructed. Multi-exposure image fusion with the proposed method is easy to construct and implement and can deliver, in less than a second for a set of three input images of size 512$× $ 340, competitive and compelling results versus state-of-art methods through visual comparison and objective evaluation.